Akhlak Santri di Era Globalisasi - Ahsanul Husna (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2021)
Many impacts of cultural globalization have occurred, one of which is moral degradation that has spread to various groups, especially teenagers. Such as behavior that is difficult to control, drunkenness, stubbornness, frequent fights, drinking parties, hedonist lifestyle, and deviant behavior. This can be prevented by efforts to foster morals in Islamic boarding schools. The purpose of this study is to describe how the efforts to develop the morals of students at the Mathlabul Ulum Islamic Boarding School in everyday life are to foster, educate and direct, so that the students can be better at having noble morals. This research uses a qualitative approach with a case study type. Data collection techniques through in-depth interviews, direct observation and documentation related to the research focus. The results of the study show that the efforts to develop the Ahklak Santri in the Era of Globalization, especially the Mathlabul Ulum Islamic Boarding School, are: 1) Getting used to greeting teachers and greeting students when they meet within the Islamic boarding school and outside the Islamic boarding school, 2) Familiarizing students with activities such as reading and memorizing Al- qur`an, 3) Often hold intensive study activities on Islam which are carried out once a week, Friday to be precise, 4) Conduct studies on classic books at the Mathlabul Ulum Islamic Boarding School which are carried out every night under the leadership Kyai and Ustadz take turns. The impact of Efforts to Foster Santri Morals at the Mathlabul Ulum Islamic Boarding School are: 1) Being able to instill moral values into the souls of students so that students are accustomed to being careful in behaving and communicating, 2) Increasing the discipline of students in carrying out Islamic boarding school activities, 3) Santri also more enthusiastic and passionate and obedient in participating in activities in Islamic boarding schools.